Paul and the Author of 1 Clement as Entrepreneurs of Identity in Corinthian Crises of Leadership. (March 2022) - Kujanpää, Katja
When Paul and the author of 1 Clement write letters to Corinth to address crises of leadership, both discuss Moses' παρρησία (frankness and openness), yet they evaluate it rather differently. In this article, I view both authors as entrepreneurs of identity and explore the ways in which they try to shape their audience's social identity and influence their behaviour in the crisis by selectively retelling scriptural narratives related to Moses. The article shows that social psychological theories under the umbrella term of the social identity approach help to illuminate the active role of leaders in identity construction as well as the processes of retelling the past in order to mobilize one's audience.